Host Delivered RNAi, an efficient approach to increase rice resistance to sheath blight pathogen (Rhizoctonia solani) - Ila Mukul Tiwari (Nature Portfolio, 2017)
Abstract Rhizoctonia solani, the causal agent of rice sheath blight disease, causes significant losses worldwide as there are no cultivars providing absolute resistance to this fungal pathogen. We have used Host Delivered RNA Interference (HD-RNAi) technology to target two PATHOGENICITY MAP KINASE 1 (PMK1) homologues, RPMK1-1 and RPMK1-2, from R. solani using a hybrid RNAi construct. PMK1 homologues in other fungal pathogens are essential for the formation of appressorium, the fungal infection structures required for penetration of the plant cuticle, as well as invasive growth once inside the plant tissues and overall viability of the pathogen within the plant. Evaluation of transgenic rice lines revealed a significant decrease in fungal infection levels compared to non-transformed controls and the observed delay in disease symptoms was further confirmed through microscopic studies. Relative expression levels of the targeted genes, RPMK1-1 and RPMK1-2, were determined in R. solani infecting either transgenic or control lines with significantly lower levels observed in R. solani infecting transgenic lines carrying the HD-RNAi constructs. This is the first report demonstrating the effectiveness of HD-RNAi against sheath blight and offers new opportunities for durable control of the disease as it does not rely on resistance conferred by major resistance genes.